SAT0181 : Antibodies to RO60 (SSA) – Can We Use Them to Monitor Disease Activity?. (10th June 2014) - Sumpton, D.J.; Weinholt, L.; Richards, B.; Youssef, P.; Adelstein, S.
Abstract : Background: Antibodies to extractable nuclear antigens (ENAs) are traditionally thought to remain stable throughout the disease course of many connective tissue diseases. As such they are usually reported as being either "positive" or "negative" and are not repeated by clinicians to track disease activity. These antibodies can now be more accurately quantified using immunoblotting techniques to give an optical density. To date, few studies have analysed whether using these new techniques will show a fluctuation in ENA antibody levels and whether any such change correlates with disease activity. In patients with systemic lupus erythematosus (SLE), small studies with conflicting results have been reported regarding the fluctuation and clinical significance of antibody levels to Ro60. Objectives: The objective of this study was to determine if levels of Ro60 antibodies fluctuate and if so, whether any change in level correlates with a change in disease activity in patients with systemic lupus erythematosus (SLE). Methods: We performed a retrospective study and firstly identified all positive Ro60 antibodies measured using immunoblotting techniques at Royal Prince Alfred Hospital, Sydney from January to December 2012. The anti-Ro60 levels were analysed to determine if there was variation between patients. We next identified all Ro60 antibodies with a positive repeat from June 2011 to September 2013 and analysed them for variation in level. Finally demographic, clinical and laboratory information was collected from the SLE patient's medical records with samples classified as either being "active" or "inactive" using a retrospective SLEDAI-SELENA modification. We used IBM SPSS Statistics to perform receiver operating characteristic curve analysis to identify if there was any correlation with antibody level and disease activity Results: In the first part of the study, we collated the levels of two hundred and nineteen positive Ro60 antibodies. We found a large variation of antibody levels which approached a normal distribution, ranging from an optical density of 10 to 130. There were forty seven patients identified who had at least one repeat Ro60 antibody performed. Twenty-six of these patients had systemic lupus erythematosus as their primary diagnosis. There was no statistically significant change in level amongst the group as a whole; however individual patients within the group had large variations in antibody level. Receiver operating characteristic curve analysis to determine whether antibody levels predicted disease activity showed that dsDNA AUC was 0.76 [95% CI: 0.58 – 0.94] while the AUC for Ro60 was 0.62 [95% CI: 0.45 – 0.80]. Conclusions: Overall, we demonstrated that there is variation in levels of antibody to Ro60 between patients and there is variation in antibody level within individual patients over time. Double stranded DNA antibody titre correlated well with disease activity but Ro60 level was a poor indicator of disease activity in patients with systemic lupus erythematosus. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2774